Fabrication of ceramic micro-scale hollow components by micro-powder injection moulding - Attia, Usama M.; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2012)
Rapid developments in microsystem technologies demand ceramic microcomponents of increasing geometrical complexity. State-of-the-art microfabrication routes of ceramics are either limited in geometrical complexity and/or high volume capabilities. This paper presents a process route by which ceramic microcomponents with relatively complex three-dimensional architectures could be realised by a high-volume technique. The proposed strategy, in which yttria- stabilised zirconia was implemented, combines the capabilities of insert- micromoulding, powder micro-overmoulding, catalytic debinding and sintering. The produced architectures demonstrate the capability of the technique to combine the high performance of ceramic materials with the dimensional accuracy and mass manufacturability of powder micromoulding.
Keywords: Injection moulding; ZrO2; Microfabrication; Functional applications